Perfil epidemiológico dos exames citopatológicos de colo de útero em Altamira entre os anos de 2014 e 2020: um estudo a partir de dados do Sistema de Informação do Câncer (SISCAN) - COLAÇA, Bianca de Assunção (2022)
This work shows characteristics related to cervical cytopathological test in Altamira, collected in the Cancer Information System, within the period from 2014 to 2020, shows the preventive exam that serves as screening for cervical cancer, whose importance is in the prevention in primary care in view of the high coverage rate of Pap smear. It was also observed the quality of interpretation of the main results found, on the collection technique and quality of exams. In view of this, the objective is to analyze the epidemiological profile of cervical cytopathological exams in the city. METHOD: the methodology used was a quantitative, cross-sectional, epidemiological study with a retrospective, descriptive and analytical approach. RESULT: As a result, there was an annual growth in the coverage rate of preventive exams in the period from 2014 to 2019, which is linked to the implementation of the Xingu Sustainable Regional Development Plan, and that this growth shows a statistically significant difference between the rate of coverage of Altamira, Pará, Brazil. It was observed the presence of failures in filling out the notification form referring to the field of education of patients who do not have a record. As for the most frequent age group that perform the preventive exam is between 25 and 34 years old and the most frequent intraepithelial lesions of the uterine cervix are: low-grade which corresponds to the young population (<34 years) and high grade between 25 to 44 years old. CONCLUSION: It is concluded that epidemiological are essential for to know the context of a disease or conditions related to it and, based on that, to develop public strategies to combat and prevent this disease, so that health managers direct strategies to attract patients in addition to knowing the weaknesses in health care and, so, directing training processes to these professionals responsible for each step of the process of this test.